Effect of post curing temperature on mechanical properties of a flax fiber reinforced epoxy composite. (April 2018) - Campana, Charlotte; Leger, Romain; Sonnier, Rodolphe; Ferry, Laurent; Ienny, Patrick
Abstract: Achieving a complete curing of biocomposites without damaging fibers is very challenging. This study assesses the impact of processing upon the mechanical properties of a unidirectional flax reinforced epoxy composite and identifies which component (resin, reinforcement or interphase) is the most sensitive to post-curing at high temperature (100, 120 or 150 °C). Post-curing temperature had a limited impact on the composite mechanical behavior excepted at 150 °C where ultimate stress and strain decreased drastically while the stabilized modulus slightly increases. Post curing is responsible of a slight decrease of the matrix tensile properties attributed to the polymer oxidation but cannot explain on its own the evolution of the composite behavior. Interfacial adhesion played a minor role in the composite behavior probably due to its intrinsic weakness. Finally, the flax fabric was highlighted to be the component most sensitive to thermal treatment thus governing the drop in the composite mechanical properties.